(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acute respiratory disorders in children are a pressing problem in modern emergency pediatrics. Their share in the structure of primary morbidity is about 60%. Acute laryngotracheitis is one of the most common and most severe manifestations of respiratory infections in children under 6 years of age, as well as one of the main causes of respiratory failure. The incidence does not tend to decrease, and a significant proportion of patients (from 30 to 50%) experience repeated and multiple episodes of laryngeal stenosis.